2020
DOI: 10.1111/jac.12391
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic and respiratory response of potato leaves of different ages during and after an episode of high temperature

Abstract: Little is known about net photosynthetic rates (Pn) of potato during and after the end of a high-temperature episode. We investigated Pn of potato leaves exposed to a high-temperature episode. Plants were grown in the greenhouse at 22°C. Shortly after tuber initiation, plants were transferred to 30°C for 9 days and then returned to 22°C. High temperatures reduced Pn of older leaves but not of the youngest leaves.Effects were transitory; Pn of leaf 7 initially fell, but then increased to be higher than the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
2
1
0
Order By: Relevance
“…In the presence of thylakoid membrane damage, electron transfer and adenosine triphosphate phosphate synthesis are diminished, along with changes in photochemical reactions [ 24 ]. Our study showed that moderate and severe HS significantly reduced chlorophyll fluorescence parameters (Fv/Fm, ETR and qP) whilst substantially increasing NPQ, which agrees with earlier findings results in wheat, potato, tomato and other crops [ 22 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the presence of thylakoid membrane damage, electron transfer and adenosine triphosphate phosphate synthesis are diminished, along with changes in photochemical reactions [ 24 ]. Our study showed that moderate and severe HS significantly reduced chlorophyll fluorescence parameters (Fv/Fm, ETR and qP) whilst substantially increasing NPQ, which agrees with earlier findings results in wheat, potato, tomato and other crops [ 22 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…Under drought stress, stomatal factors are less regulated in aged leaves than in fully expanded young leaves. This senescence leads to a stronger inhibition of non‐stomatal factors in aged leaves than in fully expanded young leaves, which agrees with previous reports (David et al, 1998; Obiero et al 2020). Leaf senescence causes an increase in nonstomatal factor contributions to suppress P n under drought stress.…”
Section: Discussionsupporting
confidence: 93%
“…At the same time, the harmful effects of heat stress can be dependent not only on the damage of the photosynthetic apparatus but also on the activity of its defense and repair mechanisms (Murata et al 2007;Ivanov et al 2017). Moreover, not only the duration and quantity of heat stress determine the effects on photosynthesis but also the sensitivity of the tested plant genotypes or the developmental stages of the exhibited organs (Zhang et al 2012;Ruocco et al 2019;Obiero et al 2020). From this aspect, the photosynthetic thermotolerance and energy-dependent defense responses of plants upon heat stress can be mediated by several phytohormones such as abscisic acid (ABA), jasmonic acid (JA) (Hu et al 2020), or ET (Figs.…”
Section: Involvement Of Ethylene In the Regulation Of Photosynthetic Components Under Heat Stressmentioning
confidence: 99%